Some aspects of the ecology of freshwater algae in the Densu River and two tributaries in Southern Ghana - Annang, Ted Y; Yirenya-Tawiah, RD; Clerk, GC; Smith, Thomas (International Journal of Environment, 2014)
Studies on the composition and abundance of the phytoplankton in River Densu and two of its tributaries, Rivers Adeiso and Nsakir were carried out at ten sampling sites, including seven from different regions of the river basin namely Afuaman, Akwadum, Densuso, Manhean, Machigeni, Nsawam and Weija, as well as Adeisoand Pokuase. Sampling was done monthly at each sampling site from January to December, 2006. Physical and chemical parameters of river water were studied. The parameters of the river water varied with the sampling sites and the time of the year. Water samples for phytoplankton identification and enumeration were collected at each sampling site. Physico-chemical conditions of the river were assessed during sample collection or in the laboratory. Correlation analysis showed that there was a positive correlation between algal genera and the measured physical and chemical parameters of the river water. DOI: http://dx.doi.org/10.3126/ije.v3i2.10637 International Journal of the Environment Vol.3(2) 2014: 246-257